2006
DOI: 10.1073/pnas.0510496103
|View full text |Cite
|
Sign up to set email alerts
|

Hsp70 chaperones accelerate protein translocation and the unfolding of stable protein aggregates by entropic pulling

Abstract: Hsp70s are highly conserved ATPase molecular chaperones mediating the correct folding of de novo synthesized proteins, the translocation of proteins across membranes, the disassembly of some native protein oligomers, and the active unfolding and disassembly of stress-induced protein aggregates. Here, we bring thermodynamic arguments and biochemical evidences for a unifying mechanism named entropic pulling, based on entropy loss due to excluded-volume effects, by which Hsp70 molecules can convert the energy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
192
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(212 citation statements)
references
References 51 publications
14
192
2
1
Order By: Relevance
“…Previous studies have shown that DnaK and Ssc1 can reactivate stable protein aggregates when assisted by bacterial DnaJ and GrpE co-chaperones (De Los Rios et al 2006;Mogk et al 1999). However, the ability of mortalin to reactivate preformed protein aggregates has not been demonstrated so far.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies have shown that DnaK and Ssc1 can reactivate stable protein aggregates when assisted by bacterial DnaJ and GrpE co-chaperones (De Los Rios et al 2006;Mogk et al 1999). However, the ability of mortalin to reactivate preformed protein aggregates has not been demonstrated so far.…”
Section: Resultsmentioning
confidence: 98%
“…This particular function of the chaperone occurs through association of the ATP-bound state to the TIM23 import channel, by way of the specific protein anchors, Tim44 and PAM16/18. Dissociation of ADP-bound Ssc1 from the anchors takes place as soon as it has locked onto an incoming polypeptide (De Los Rios et al 2006;D'Silva et al 2004;Neupert and Herrmann 2007). Ssc1 plays an additional important role in mediating the refolding of matrix-localized proteins, a function which is carried out with the help of two matrix-localized co-chaperones Mdj1 and Mge1, which are homologous to the Escherichia coli DnaJ and GrpE, respectively (Deloche et al 1997;Horst et al 1997;Liu et al 2001;Rowley et al 1994) (Supplemental Fig.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas Hsp70/40 is essential for Hsp104 protein disaggregation, the mechanistic role of Hsp70 remained unclear. It has been reported that Hsp70/40 possesses some protein disaggregating activity (45), which can be stimulated by Hsp110 (an Hsp70-related nucleotide exchange factor of Hsp70), but which is less efficient than the Hsp104 bichaperone system (46).…”
Section: Discussionmentioning
confidence: 99%
“…While there is some information available on the role that Hsp72 plays in chaperoning proteins through intracellular membranes (De Los Rios et al 2006) and remodeling complex protein structures such as clathrin-coated pits (Prasad et al 1994), the effect of Hsp72 on intracellular signaling remains largely undefined. Hsp72 has been shown to bind to a variety of different kinases and signaling molecules, and so may have an impact on a number of different aspects of cell regulation including the cell cycle (Diehl et al 2003) and p53 signaling (Fourie et al 1997).…”
Section: Discussionmentioning
confidence: 99%